Gambaran Morbiditas Premenstrual Syndrome dan Tingkat Kecemasan pada Remaja Putri - Qotrunada, Haning Tyas; Linggardini, Kris (Faletehan Health Journal, 2023)
Premenstrual Syndrome (PMS) is one of the most common disorders among women. The prevalence of PMS worldwide is about 48% in women of reproductive age, while in Indonesia, the prevalence reaches 80-90%, with perceived severe symptoms. Anxiety is an emotional occurrence in women and is a distinctive symptom of stress. The incidence of anxiety due to PMS is approximately 20% of the world's population, and in Indonesia, anxiety related to PMS is estimated to range from 9% to 12%. This study aims to assess the morbidity of Premenstrual Syndrome (PMS) and anxiety levels in adolescent girls. The method used is quantitative descriptive with a cross-sectional approach. The sample consists of 76 female students from grade VII and VIII in SMPN 2 Sokaraja, who completed the sPAF and DASS-42 questionnaires. The results show that the respondents experienced symptoms of easy irritability/anger (61.2%), with mild (30.3%), moderate (43.4%), and severe (25%) levels of PMS, while anxiety levels varied from normal (32.9%) to mild (15.8%), moderate (17.1%), severe (15.8%), and panic (18.4%). This study recommends the necessity of health campaigns on PMS and anxiety in adolescent girls to reduce stigma and enhance public understanding.